Potential Use of Carrageenans against the Limestone Proliferation of the Cyanobacterium Parakomarekiella sesnandensis - Soares, Fabiana (2021)
Stone biodeterioration by cyanobacteria is a common issue in the field of cultural heritage. As they are considered the first stone colonizers, the need to control their growth has increased. In this study, we evaluated the effectiveness of kappa/iota carrageenans from the red seaweed Chondracanthus teedei var. lusitanicus against the limestone proliferation of the cyanobacterium Parakomarekiella sesnandensis, under laboratory conditions. For this purpose, 200 L of kappa/iota carrageenans (0.01 g mL1) were applied into the surface of the limestone replicas prior to their inoculation with P. sesnandensis. Results were evaluated after 4 months of incubation through visual inspection, stereomicroscopy, scanning electron microscopy and colorimetric analyses. The gathered data demonstrated that these types of carrageenans have the potential to reduce the colonization of P. sesnandensis. With one sole application, the aesthetical alterations caused by the proliferation of P. sesnandensis were drastically reduced. This study highlights the need to explore marine-based products, particularly those derived from seaweeds with antimicrobial properties, as alternative methods for biocleaning cultural heritage assets.